Cerebrospinal fluid neurofilament light levels in neurodegenerative dementia: Evaluation of diagnostic accuracy in the differential diagnosis of prion diseases. Issue 6 (29th January 2018) - Zerr, Inga; Schmitz, Matthias; Karch, André; Villar‐Piqué, Anna; Kanata, Eirini; Golanska, Ewa; Díaz‐Lucena, Daniela; Karsanidou, Aikaterini; Hermann, Peter; Knipper, Tobias; Goebel, Stefan; Varges, Daniela; et al.
Abstract: Introduction: Neurofilament light (NFL) levels in the cerebrospinal fluid are increased in several neurodegenerative dementias. However, their diagnostic accuracy in the differential diagnostic context is unknown. Methods: Cerebrospinal fluid NFL levels were quantified in nonprimarily neurodegenerative neurological and psychiatric diseases (n = 122), mild cognitive impairment (n = 48), Alzheimer's disease (n = 108), dementia with Lewy bodies/Parkinson's disease dementia (n = 53), vascular dementia (n = 46), frontotemporal dementia (n = 41), sporadic Creutzfeldt‐Jakob disease (sCJD, n = 132), and genetic prion diseases (n = 182). Results: The highest NFL levels were detected in sCJD, followed by vascular dementia, frontotemporal dementia, dementia with Lewy bodies/Parkinson's disease dementia, Alzheimer's disease, and mild cognitive impairment. In sCJD, NFL levels correlated with cerebrospinal fluid tau and disease duration. NFL levels were able to differentiate sCJD from nonprimarily neurodegenerative neurological and psychiatric diseases (area under the curve = 0.99, 95% confidence interval: 0.99–1) and from the other diagnostic groups showing cognitive impairment/dementia of a non‐CJD etiology (area under the curve = 0.90, 95% confidence interval: 0.87–0.92). Compared to nonprimarily neurodegenerative neurological and psychiatric diseases, NFL was also elevated in genetic prion diseases associated with the E200K, V210I, P102L, and D178N prion protein gene mutations. Discussion: Increased NFL levels are a common feature in neurodegenerative dementias.